2020
DOI: 10.1155/2020/8851480
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of EFEMP1 in the Hippocampus May Be Related to the Deficit in Spatial Memory of Rat Neonates Triggered by Repeated Administration of Propofol

Abstract: It has been confirmed that repeated application of propofol, as an intravenous and short-fast-acting anesthetic, in neonatal animals or humans may produce long-term deficits in cognitive functions. With the aim of explaining the neurotoxic effects of repeated administration of propofol on neonatal rat pups from P7 to P9 especially from an epigenetic perspective, the present study used the Morris water maze to detect cognitive deficits in spatial learning and memory, Sequenom methylation on the CpG island locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Therefore, we speculate that the increase in EFEMP1 may be associated with the increase in EGFR and VEGF during myopia development. Moreover, EFEMP1 is important for maintaining the integrity of the basement membrane and the binding of other extracellular matrices, such as elastic fibers and basement membranes ( Zhang et al, 2020 ). Some researchers have found that EFEMP1 interacts with elastin as well as collagen 15A1 (a component of collagen fibrils) to produce proteins that affect the expression and function of these proteins ( Jorgenson et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that the increase in EFEMP1 may be associated with the increase in EGFR and VEGF during myopia development. Moreover, EFEMP1 is important for maintaining the integrity of the basement membrane and the binding of other extracellular matrices, such as elastic fibers and basement membranes ( Zhang et al, 2020 ). Some researchers have found that EFEMP1 interacts with elastin as well as collagen 15A1 (a component of collagen fibrils) to produce proteins that affect the expression and function of these proteins ( Jorgenson et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fibulin-3 can upregulate tissue inhibitors of metalloproteinase-1 (TIMP-1) and TIMP-3 and downregulate metalloproteinase-2 (MMP-2), MMP-3, and MMP-9. These factors are digestive enzymes of protein that participate in maintaining ECM and regulating learning and memory. , A study found that propofol exposure for 3 consecutive days from PND 7 to PND 9 in rats can lead to hypermethylation of CpG sites in the EFEMP1 promoter region, decrease the expression of fibulin-3 and TIMP-3, and increase the expression of MMP-9, thus interfering with the stability of ECM in the hippocampus and leading to growth retardation and cognitive impairment …”
Section: Mechanisms Of Propofol-induced Developmental Neurotoxicitymentioning
confidence: 99%
“…97,98 A study found that propofol exposure for 3 consecutive days from PND 7 to PND 9 in rats can lead to hypermethylation of CpG sites in the EFEMP1 promoter region, decrease the expression of fibulin-3 and TIMP-3, and increase the expression of MMP-9, thus interfering with the stability of ECM in the hippocampus and leading to growth retardation and cognitive impairment. 99 3.8. Brain Region-Specific Neurotoxicity.…”
Section: Abnormal Synaptogenesis and Neuronal Circuitmentioning
confidence: 99%